Usability Evaluation of Four Top-Rated Commercially Available Diabetes Apps for Adults With Type 2 Diabetes. Issue 6 (June 2020) - Fu, Helen N. C.; Rizvi, Rubina F.; Wyman, Jean F.; Adam, Terrence J.
Abstract : Despite the many diabetes applications available, the rate of use is low, which may be associated with design issues. This study examined app usability compliance with heuristic design principles, guided by the Self-determination Theory on motivation. Four top-rated commercially available apps ( Glucose Buddy, MyNetDiary, mySugr, and OnTrack ) were tested for data recording, blood glucose analysis, and data sharing important for diabetes competence, autonomy, and connection with a healthcare provider. Four clinicians rated each app's compliance with Nielsen's 10 principles and its usability using the System Usability Scale. All four apps lacked one task function related to diabetes care competence or autonomy. Experts ranked app usability rated with the System Usability Scale: OnTrack (61) and Glucose Buddy (60) as a "D" and MyNetDairy (41) and mySugr (15) as an "F." A total of 314 heuristic violations were identified. The heuristic principle violated most frequently was "Help and Documentation" (n = 50), followed by "Error Prevention" (n = 45) and "Aesthetic and Minimalist Design" (n = 43). Four top-rated diabetes apps have "marginally acceptable" to "completely unacceptable." Future diabetes app design should target patient motivation and incorporate key heuristic design principles by providing tutorials with a help function, eliminating error-prone operations, and providing enhanced graphical or screen views.